Sogit, is still relevant to be applied in this era / Azeah Said and Norleja Waslee - Said, Azeah; Waslee, Norleja (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2003)
This research is on the appropriation of the application of the custom law known as "sogit" in this modem era. This research will focus on the resident of Kampung Bayangan, Kampung Menawo, in Keningau, Kampung Dambai, and Kampung Dungkahang in Penampang and the Native Court in Keningau. This includes time spent for heading, the age's differences, that give various opinions, what the usual cases that relating to "sogit" and how beneficial it is to the people. Research will only conducted opinion whether is it still relevant if the custom law had been applied today and the appropriation regarding to that situation. Studies will be conducted on KadazanDusun and Dusun races, as they are the ones more involved in. this custom law than other races. People especially those live in rural area are still applying this law. Therefore, we picked this particular race because it suits the research the most. Research on this particular subject is not common and it is certainly very complicated. We do not find any local accounts on research regarding the application at this law. Therefore; this research hopes to answer all the question arises from this particular topic . Last but not least team members. Co-operations, moral support, sharing pain, sweat and thought are the ingredients to a successful group and teamwork. As a result, this research is the proof of the hard work we both went through together. All things made it easy when there's a helping hand. Thank you for everything and we both will always remember this as a pleasant memory. Thank you all for your help, support, guidance, encouragement's and loves. We cherish this for the rest in our life. May Allah bless you all and may the entire blessing in this world showers upon you always.